2015
DOI: 10.1177/1087054715617533
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Effects of ADHD Subtypes in Patients With Social Anxiety Disorder

Abstract: The inattentive subtype of ADHD may have a more specific relationship with SAD than ADHD-C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 44 publications
2
19
0
Order By: Relevance
“…Fear/anxiety, avoidance, and total scores of Liebowitz Social Anxiety Scale (LSAS) and lifetime major depressive disorder were found to be higher and functionality was found to be lower in the group of patients with comorbid ADHD, when compared with those without ADHD. In their second study, Koyuncu et al (2015b) found the rate of childhood ADHD comorbidity as 62% (n=88) in patients with SAD (n=142), and 63 of these patients had the diagnosis of inattentive type. This group had higher scores of social anxiety and avoidance and had earlier onset of SAD than the combined type of childhood ADHD.…”
Section: Introductionmentioning
confidence: 97%
“…Fear/anxiety, avoidance, and total scores of Liebowitz Social Anxiety Scale (LSAS) and lifetime major depressive disorder were found to be higher and functionality was found to be lower in the group of patients with comorbid ADHD, when compared with those without ADHD. In their second study, Koyuncu et al (2015b) found the rate of childhood ADHD comorbidity as 62% (n=88) in patients with SAD (n=142), and 63 of these patients had the diagnosis of inattentive type. This group had higher scores of social anxiety and avoidance and had earlier onset of SAD than the combined type of childhood ADHD.…”
Section: Introductionmentioning
confidence: 97%
“…19 High rates of co-morbidity in patients with SAD may indicate a more specific ADHD and SAD relationship. 3,4 Moreover, in studies of ADHD, SAD has been reported to have a high prevalence as a comorbid anxiety disorder. 9,10 All these studies may provide evidence supporting our hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…In the first study, 72.3% of 130 outpatients with a primary diagnosis of adult SAD also met the diagnostic criteria for childhood ADHD . The second study showed that 62.1% had childhood ADHD in a sample of 142 outpatients with SAD …”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Therefore, it may be important to know the prevalence and patterns of psychiatric comorbidity and sleep problems and their relationship between clinical (such as ADHD presentation) and sociodemographic (such as age and gender) variables in young subjects with ADHD. Despite there having been several reports on the prevalence and patterns of comorbid psychiatric disorders in relation to different ADHD presentations, age and gender among adults with ADHD, there is a lack of studies on these issues among young subjects with ADHD (18,19). In this study, the researchers investigated the prevalence and patterns of psychiatric comorbidity and sleep problems in relation to different ADHD presentations, age (children vs adolescents), and gender in a clinical sample of children and adolescents with ADHD.…”
Section: Introductionmentioning
confidence: 99%